DEVELOPMENT OF STUDENT LEARNING MEDIA BASED ON MEDICAL RECORD INFORMATION SYSTEM - Musparlin Halid; Aria Yulandita; Ikhwan (UNIVERSITAS STEKOM, 2023)
In order to improve the quality and quantity of the learning process, the Medical Records Laboratory has supporting facilities, so that each student can carry out the practice of managing medical record documents and information in accordance with their competence. Information technology-based information systems are currently not available in the Medical Records Laboratory, so that when students do practicum it is not effective and efficient, therefore the availability of information technology-based information systems needs to exist. This study aims to determine the design of information systems, and build a medical record laboratory information system at Medica Farma Husada Mataram Polytechnic, including: Old and alternative system design, Database Design, ERD (Entity Relational Diagram), UML (Unified Modeling Language) Design, Interface Implementation. This research is qualitative research using the waterfall method. The results showed that the hierarchy of the information system for the Medical Records Laboratory of the Medica Farma Husada Mataram Polytechnic was made by the Php program and was also accompanied by the use of a MySQL database integrated with a good security system. The process consists of Patient Registration, Polyclinic Data Collection, Doctor Data Collection, Drug Data Collection, and the Output consists of Patient data reports, Print Out Pasie data, Polyclinic data reports, Doctor data reports, Drug Data Reports. The conclusion of this research is that the design of an information system-based Medical Records Laboratory consists of 3 menus, namely patients, doctors and medical records officers.